Identification of an Integrase That Responsible for Precise Integration and Excision of Riemerella anatipestifer Genomic Island - Wang, Ying; Zhang, Yang; Cui, Yijie; Sun, Zhijian; Zhou, Zutao; Hu, Sishun; Li, Shaowen; Liu, Mei; Meng, Xianrong; Xiao, Yuncai; Shi, Deshi; Bi, Dingren; et al. (Frontiers in Microbiology, 2019)
Riemerella anatipestifer is a Gram-negative, pathogenic bacterium, which is harmful to poultry. However, the genomic islands (GIs) in R. anatipestifer are not well-studied. In this study, a 10K genomic island was predicted by the bioinformatics analysis of R. anatipestifer ATCC11845, which is widely found in other R. anatipestifer genomes. We had first reported the genomic island integration and excision function in R. anatipestifer. We successfully constructed the integration plasmid by using the integrase and 53 bp attP elements. The 10K GI was found integrated at the 53 bp attB located in the Arg-tRNA of the R. anatipestifer YM chromosome. We identified an integrase that helped in the precise integration and excision in R. anatipestifer and elucidated the molecular mechanism of the 10K genomic island integration and excision. Furthermore, we provided a new method for the gene expression and construction of complementary strain.